2019
DOI: 10.3390/v11080717
|View full text |Cite
|
Sign up to set email alerts
|

Middle East Respiratory Syndrome Coronavirus (MERS-CoV) in Dromedary Camels in Africa and Middle East

Abstract: : Dromedary camels are the natural reservoirs of the Middle East respiratory syndrome coronavirus (MERS-CoV). Camels are mostly bred in East African countries then exported into Africa and Middle East for consumption. To understand the distribution of MERS-CoV among camels in North Africa and the Middle East, we conducted surveillance in Egypt, Senegal, Tunisia, Uganda, Jordan, Saudi Arabia, and Iraq. We also performed longitudinal studies of three camel herds in Egypt and Jordan to elucidate MERS-CoV infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 27 publications
2
45
2
1
Order By: Relevance
“…Dromedary camels are a host reservoir species for the MERS-CoV (appendix pp 3-5). [20][21][22][23] Humans can acquire MERS-CoV through direct or indirect contact with infected dromedary camels or infected patients [19][20][21][22][23][24][25][26][27][28][29][30] (figure 4A). However not all cases infected in the community report contact with dromedary camels (appendix p 4-5).…”
Section: Sources Of Infectionmentioning
confidence: 99%
“…Dromedary camels are a host reservoir species for the MERS-CoV (appendix pp 3-5). [20][21][22][23] Humans can acquire MERS-CoV through direct or indirect contact with infected dromedary camels or infected patients [19][20][21][22][23][24][25][26][27][28][29][30] (figure 4A). However not all cases infected in the community report contact with dromedary camels (appendix p 4-5).…”
Section: Sources Of Infectionmentioning
confidence: 99%
“…Coronaviruses, in particular, are addressed in three papers. Kandeil et al [1] demonstrate a high seroprevalence of MERS coronavirus in adult dromedary camels from Asia and Africa, and Alsaadi et al [2] characterize a fusion peptide in the spike protein of MERS-CoV. Avian coronaviruses are also addressed in the article from Fan et al [3], which reveals the changes in genetic diversity, dominant genotypes, and selection pressure on the bronchitis virus (IBV) circulating in yellow chickens in China.…”
mentioning
confidence: 99%
“…In a recent study from Egypt, Senegal, Tunisia, Uganda, Jordan, Saudi Arabia, and Iraq, MERS-CoV was detected in camels using either PCR or serology. 156 The positivity rate using PCR ranged from 0% in Uganda, Jordan, and Iraq to 3.1% in Saudi Arabia, 5.5% in Senegal, and 8.2% in Egypt. 156 It was shown that seropositivity is very high (84.5%) among tested camels compared with PCR positivity of 3.8%.…”
Section: Mers and Camel Connectionsmentioning
confidence: 98%